Determinant of the Labor Force, Electricity Consumption, and Clean Water on Economic Growth in Indonesia 2014-2019 - Hira Davika; Hastarini Dwi Atmanti (Global Economics: International Journal of Economic, Social and Development Sciences, 2024)
This research was conducted to determine the extent of the impact of the workforce, electricity consumption, and clean water consumption on economic growth in Indonesia. The data in this study is secondary data obtained from the publications of the Central Bureau of Statistics Indonesia for the years 2014-2019. This research uses the Ordinary Least Square (OLS). From the results of this Ordinary least Square analysis, it was found that the labor force variable does not affect economic growth. Meanwhile, the variables of electricity consumption and clean water consumption do affect economic growth. From the F-statistic probability result of 0.000000 < the significance level of 0.05, it can be concluded that together, these three variables affect economic growth. The three variables in this study simultaneously influence economic growth by 99.51%.